Evaluasi dan Perbaikan Aplikasi Mobile Malang Menyapa Menggunakan Metode Usability Testing dan USE Questionnaire - Dinda Hudaifa; Ismiarta Aknuranda; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Malang Menyapa is a mobile application released by Malang City Culture and Tourism Service in order to develop the cultural and tourism potential of Malang City. This application has seven main features, including Destination, Shopping, Hotel, Food, Souvenir, Travel and Entertainment. Malang Menyapa mobile application has been downloaded 5 thousand times and the rating is 4.3. But users think that the application has problems, for example the user interface is less attractive, font and content design are deemed inappropriate. Another problem related to maps that only displays the destination without displaying distances and routes. There is no search coloumn, the layout are messy and confusing. Therefore, it is necessary to evaluate usability and explore the problems found in the Malang Menyapa mobile application. The method is usability testing and USE Questionnaire. There are two tests in this study, initial test and final test after improvement recommendations. Based on testing, the result are usability value for initial testing is 60.27% with SUFFICIENT predicate. And the final test produced 73.68% with GOOD predicate.